The Impact of Antibiotic Awareness on Usage Among University Students in Kabul, Afghanistan - Zia Ur Rahman Zia; Farkhunda Khodayar; Hadia khodayar; Tamanna Quraishi (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Antibiotic resistance poses a significant global health challenge, exacerbated by inappropriate self-medication practices. This study explores the level of awareness and practices concerning antibiotic use among university students in Afghanistan. The research aimed to evaluate university students' knowledge of antibiotic resistance, their self-medication behaviors, and overall understanding of appropriate antibiotic use. The goal was to identify gaps in knowledge and inform strategies for educational interventions. An online survey was administered via Google Forms to 150 students from various provinces in Afghanistan. Participants were selected to represent a diverse geographical distribution, including Kabul (35.71%) and seven other provinces. The survey assessed participants' knowledge about antibiotics, awareness of resistance risks, and self-medication practices. The survey results indicated a moderate level of awareness about antibiotic resistance among students. Despite this, many students reported engaging in self-medication. Knowledge deficiencies were observed regarding the proper use of antibiotics and the implications of resistance. The study found significant variability in understanding, with some students showing high confidence while others lacked basic knowledge. The study underscores the need for targeted educational programs to improve awareness and correct misconceptions about antibiotics among university students. Addressing these knowledge gaps is essential for promoting responsible antibiotic use and combating resistance. Future research should evaluate the impact of such educational interventions on altering self-medication behaviors and enhancing antibiotic stewardship.